Effect of Home-Based Cardiac Rehabilitation Program on Self-Efficacy of Patients With Implantable Cardioverter Defibrillator - Mohammad Heidari PhD; Parviz Nadimi Harandi MSc; Jaefar Moghaddasi PhD; Soleiman Kheiri PhD; Amirhossein Azhari PhD (SAGE Publishing, 2023)
Introduction For more effective control and treatment of cardiac dysrhythmias caused by diseases, ischemia, or other causes, an implantable cardioverter defibrillator (ICD) is used. One of the effective ways for secondary prevention is the home-based cardiac rehabilitation (HBCR) which nurses have an effective role in its implementation. Objective The study aimed to investigate the effect of implementing HBCR programs on the self-efficacy of patients with ICD. Methods This is a semi-experimental study conducted on 70 patients who received ICD in Shahid Chamran Heart Center of Isfahan University of Medical Sciences (IUMS) in 2021. The patients were randomly assigned to intervention and control groups and were introduced to the practical concepts of HBCR during four training sessions. In the following, 3-month follow-up and trainings were continued by home visits, telephone follow-up, and use of social messaging networks due to the conditions of coronavirus disease 2019 (COVID-19) pandemic. The data were analyzed with SPSS/21. Results The findings showed that performing HBCR programs was effective in improving the self-efficacy of patients with ICDs. A significant trend in the implementation of the HBCR programs in two groups was shown using chi-square test and independent t -test and variance with repeated measurements ( p  < .001). There was no significant difference in self-efficacy score in both groups at the beginning of the study ( p  < .056). Conclusion Considering the effectiveness of HBCR programs on improving the self-efficacy of patients with ICDs, it can be used in the educational care programs of healthcare workers and in the strategic policies of health care services.